Teacher's motivating factors to serve in rural area school / Sharmimiee Mohd Hussain and Siti Noranum Sarip - Mohd Hussain, Sharmimiee; Sarip, Siti Noranum (2014)
Teachers that had experienced serve in rural schools are term that used in this research. This study is conducted to examine the factors motivating teachers to serve in rural area schools and to rank the factors that motivate teachers based on the gender. This research is conducted by using a simple random sampling technique where the elements in the population are selected randomly. The sample sizes for the purpose of this research are 81 respondents selected randomly that teachers serve in the rural areas schools in the Sabah district. While the data collection instrument for this research is done through questionnaires and secondary data.